Production of K[ast](892)0 and [phi](1020) in pp collisions at √s=7 TeV - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Krawutschke, Tobias; Kweon, MinJung; Lohner, Daniel; Lu, Xianguo; Mercado Pérez, Jorge; Oyama, Ken; et al. (The European physical journal. C, Particles and fields, 2012)
The production of K∗(892)0 and ϕ(1020) in pp collisions at s√=7 TeVs=7 TeV\sqrt{s}=7~\mathrm{TeV} was measured by the ALICE experiment at the LHC. The yields and the transverse momentum spectra d2 N/dydp T at midrapidity |y|<0.5 in the range 0<p T<6 GeV/c for K∗(892)0 and 0.4<p T<6 GeV/c for ϕ(1020) are reported and compared to model predictions. Using the yield of pions, kaons, and Ω baryons measured previously by ALICE at s√=7 TeVs=7 TeV\sqrt{s}=7\ \mathrm{TeV}, the ratios K∗/K−, ϕ/K∗, ϕ/K−, ϕ/π −, and (Ω+Ω¯¯¯¯)/ϕ(Ω+Ω¯)/ϕ(\Omega + \overline{\Omega })/\phi are presented. The values of the K∗/K−, ϕ/K∗ and ϕ/K− ratios are similar to those found at lower centre-of-mass energies. In contrast, the ϕ/π − ratio, which has been observed to increase with energy, seems to saturate above 200 GeV. The (Ω+Ω¯¯¯¯)/ϕ(Ω+Ω¯)/ϕ(\Omega + \overline {\Omega })/\phi ratio in the p T range 1-5 GeV/c is found to be in good agreement with the prediction of the HIJING/BB¯¯¯¯HIJING/BB¯\mathrm{HIJING}/\mathrm{B}\overline{\mathrm{B}} v2.0 model with a strong colour field.